Identification of Plasmodium falciparum RhopH3 protein peptides that specifically bind to erythrocytes and inhibit merozoite invasion (2008)
The identification of sequences involved in binding to erythrocytes is an important step for understanding the molecular basis of merozoite-erythrocyte interactions that take place during invasion of the Plasmodium falciparum malaria parasite into host cells. Several molecules located in the apical organelles (micronemes, rhoptry, dense granules) of the invasive-stage parasite are essential for erythrocyte recognition, invasion, and establishment of the nascent parasitophorous vacuole. Particularly, it has been demonstrated that rhoptry proteins play an important role in binding to erythrocyte surface receptors, among which is the Pf RhopH3 protein, which triggers important immune responses in patients from endemic regions. It has also been reported that anti-RhopH3 antibodies inhibit in vitro invasion of erythrocytes, further supporting its direct involvement in erythrocyte invasion processes. In this study, Pf RhopH3 consecutive peptides were synthesized and tested in erythrocyte binding assays for identifying those regions mediating binding to erythrocytes. Fourteen Pf RhopH3 peptides presenting high specific binding activity were found, whose bindings were saturable and presented nanomolar dissociation constants. These high-activity binding peptides (HABPs) were characterized by having a-helical structural elements, as determined by circular dichroism, and having receptors of a possible sialic acid-dependent and/or glycoprotein- dependent nature, as evidenced in enzyme-treated erythrocyte binding assays and further corroborated by cross-linking assay results. Furthermore, these HABPs inhibited merozoite in vitro invasion of normal erythrocytes at 200 mM by up to 60% and 90%, suggesting that some RhopH3 protein regions are involved in the P. falciparum erythrocyte invasion. Copyright © 2008 The Protein Society.